The Impact of Functional Strength Training on Balance Agility and Injury Prevention in Young Athletes - Alaa Hashim Ahmed (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
The purpose of this research was to determine how functional strength (FST) training over 12 weeks influenced injured young competitive athletes’ dynamic balance, agility, and incidence of injury. The project used 40 young competitive athletes (mean age = 15.3±1.2 years) as participants and was designed as a randomized controlled trial with 20 in the experimental FST group and 20 in the active control (AC) group. Balance was measured by the Star Excursion Balance Test (SEBT) composite score; agility was measured with the Illinois Agility Test (IAT) time; and the number of injuries suffered per 1000 athlete exposures (AE) was used to determine how each group differed regarding incidence of injury. Other measures included the 1-repetition maximum (1-RM) back squat for lower-body strength, joint position sense (JPS) for proprioceptive acuity, and the composite score of the Functional Movement Screen test (FMS) for quality of movement. Compared to Control an FST condition had much larger impact on SEBT composite scores (Delta 13.4% vs 4.4%: p<.001; d=2.04) and IAT (Delta 11.3% vs 4.7%: p<.001; d=1.58) as well as Injuries (Delta -60.4% vs -23.4%: p<.001; d=1.87). With all between-group effect sizes being considered large, the data strongly supports the use of FST in early phases of injury prevention and performance enhancement for youth athletes.